A Comparative Study of Infiltration Capacity on Various Land Covers in the PT Semen Padang Industrial Area - Totoh Andayono; Muhammad Din (CIVED, 2025)
Changes in land cover within industrial areas have the potential to reduce soil infiltration capacity and increase the risk of surface runoff and flooding. This study aims to analyze and compare infiltration capacities across various land cover types within the industrial area of PT Semen Padang. Infiltration measurements were conducted using the double-ring infiltrometer method on several land cover types, namely greenbelt areas, open land, and developed areas. The data obtained were analyzed using the Horton model approach to determine initial and constant infiltration rates. The results indicate that greenbelt areas exhibit the highest infiltration capacity, with an average constant infiltration rate of 183.3 mm/h, followed by open land at 74 mm/h, while built-up areas showed the lowest rate at 35.9 mm/h. These differences are influenced by soil density, organic matter content, and vegetation root activity. These findings indicate that an increase in built-up surface area significantly reduces the soil’s ability to infiltrate water, thereby potentially increasing surface runoff. This study recommends the implementation of green infrastructure and the conservation of vegetated land to support sustainable stormwater management in industrial areas.